The Effect of Principal Transformational Leadership on Teacher's Performance - Musriadi, Musriadi; Nasrun, Nasrun; Ansary, Khairil (SCAD Independent, 2022)
This study aimed to examine the teacher performance model built on associative causal relationships between exogenous variables and endogenous variables, namely; the effect of a principal's transformational leadership on job satisfaction, the effect of organizational culture, the effect of organizational climate, the effect of principal's transformational leadership to teacher performance, the effect of organizational culture, and the effect of organizational climate. This research was conducted at Junior High School in Banda Aceh City by involving 260 teachers as respondents. The Data collection was done using a questionnaire using a proportional random sampling method. The validity test used Product Moment correlation to test its reliability using the Alpha formula. Before testing the hypothesis, especially before the test was calculated, the analysis requirements included the normality data test and regression linearity test. Based on the analysis of the research hypothesis, it is revealed that a fixed model that describes the structure of causal relationships between principal's transformational leadership, organizational culture, organizational climate, job satisfaction, and teacher performance at Junior Highschool in Banda Aceh City.